Freia and komas, the central planning bureau's new generation of macro-economic policy models: a review - Butter den f.a.g (Netherland de nederlandsche bank N.V., 1985)
This book examines the Netherlands long stands on using empirical macro-economic models in decision making.
asm; 06/03/19
Loans
Keywords: Finance; Economic - finance; Netherlands